Are Data Available to Measure Progress in the Coverage of Essential Nutrition Actions in South Asia? A Review of Demographic and Health Surveys in Seven Countries, 2005–2018. (29th May 2020) - Jangid, Manita; Neupane, Sumanta; Scott, Samuel; Nguyen, Phuong; Kim, Sunny; Menon, Purnima; Torlesse, Harriet; Murira, Zivai; Heidkamp, Rebecca
Abstract: Objectives: South Asian countries carry the largest burden of undernutrition globally. The World Health Organization has recommended a set of Essential Nutrition Actions (ENA) to tackle all forms of malnutrition. Limited evidence exists on the availability of data in nationally representative surveys to analyse coverage patterns and to track progress on these actions. Methods: We reviewed household and woman questionnaires from DHS surveys conducted in South Asia—Afghanistan (2014), Bangladesh (2011 and 2014), India (2006 and 2016), Maldives (2009 and 2017), Nepal (2011 and 2016), Pakistan (2013 and 2018), and Sri Lanka (2006 and 2016)—to assess the availability of data to track coverage of the ENAs in South Asia region. For each ENA, we examined questionnaires to identify the availability of questions that could be used to construct coverage indicators. Results: For adolescents and women of reproductive age, DHS questionnaires ask about prenatal iron folic acid (IFA) supplementation in zero countries and use of iodized salt in five countries. For pregnant women, out of six recommended ENAs, five are measured in at least one country: health and nutrition education, energy and protein supplementation, IFA supplementation, calcium supplementation, and multiple micronutrients that contain IFA. For postpartum women, data on iron supplementation and breastfeeding counselling are collected in only four countries. For early childhood, DHS surveys only measure 6 of 25 ENAs; only vitamin A supplementation is being tracked in DHS across all seven countries, while children who were breastfed early, had immediate skin to skin contact and zinc supplementation are measured in most countries. Conclusions: Data for more than half of the ENAs across the continuum of care are not collected in the South Asian DHS questionnaires; gaps exist both for interventions and among countries. Coverage data from household surveys are critical to enable countries to track progress towards national coverage goals and to examine equity in the reach of interventions. To support national efforts to scale-up the coverage of ENAs, national survey instruments should be reviewed to include indicators on the coverage of a broader set of ENA indicators. Funding Sources: Data for Decisions to Expand Nutrition Transformation (DataDENT) project, supported by the Bill and Melinda Gates Foundation.